Strategi Promosi Melalui Media Sosial Instagram Di Langgeng Florist Bali - Wardani, Ni Made Rima Sri Darma; Sunarsa, I Wayan; Seniartha, I Wayan (Journal of Hospitality Accommodation Management (JHAM), 2024)
Langgeng Florist Bali is one of the flower businesses in the Jimbaran area which was established in 2013 and has experienced very fast development. This development is supported by promotional strategies carried out on Instagram social media to introduce the products or services they have. The aim of this research is to determine the promotional strategy for Langgeng Florist Bali which is carried out through Instagram social media. Data collection techniques were carried out using interview and documentation methods. The data obtained was then analyzed using the SWOT analysis technique by combining internal and external factors. The research results show that the Instagram social media strategy implemented is as follows: (1) participating in events or exhibitions and posting these moments via Instagram stories. (2) working with influencers or popular accounts to collaborate to create interesting content about flowers, (3) creating interesting and creative visual content by utilizing Instagram features such as reels, guides, or shopping (4) carrying out product and service diversification strategies services such as wedding decorations, (5) identifying market segments and determining the market segments that best suit Langgeng Florist Bali's products and services.